Analysis of the spelling, effective sentences, and paragraphs in the students scientific papers - I Nyoman Mandia; I Nyoman Sukra; Putu Diyah Hudiananingsih (Politeknik Negeri Bali, 2021)
This study aims to determine the level of use of spelling, effective sentences, and Indonesian language paragraphs in scientific papers applied by undergraduate students of the State Polytechnic of Bali in the form of theses. This research is important because there is a tendency to use spelling, effective sentences, and paragraphs in student scientific papers that are not in accordance with applicable rules such as prepositions, punctuation. The method used in this study is a qualitative method, while the method of data collection in the form of documentation with qualitative descriptive analysis. Studies on spelling order, each of them scored: Managerial Accounting Study Program 98.73, International Business Study Program 98.96, Tourism Business Management Study Program 99.02, Construction Management Study Program 98.51 with an average rating of 98.80. At the sentence level each gets a value: Managerial Accounting Study Program 83.72, International Business Study Program 85.22, Tourism Business Management Study Program 77.25, and Construction Management Study Program 74.75, while at the paragraph level each value: Accounting Study Program Managerial 70.74, International Business Study Program 61.20, Tourism Business Management Study Program 60.31, and Construction Management Study Program 66.87, with an average rating of 64.78. Thus, it can be concluded that spelling ability, effective sentence, and student paragraphs applied bachelor of Polytechnic Bali is very good.